All that glitter could be green : how can internationally operating luxury fashion firms cope with sustainability? - Mazzeo, Maria Luisa (2020)
This research aims at developing the discussion on how internationally operating luxury fashion firms can cope with sustainability. To answer this research question, we conducted two case studies on two American luxury fashion firms and committed toward the sustainability issue. The results show the opportunity of working with international suppliers, the importance of defining the commitment toward sustainability as an intrinsic value for the company’s culture, the importance of balancing short-term and long-term goals and the necessity of increasing customers’ awareness without leveraging too much on prices. Finally, we suggest that a balance between financial growth of a business and it positive social and environmental impact is possible. It requires, however, a committed strategy to be properly developed.